Medical professionalism among emergency physicians in South Korea: a survey of perceptions and experiences of unprofessional behavior - Nah, Sangun; Han, Sangsoo; Park, Kyunghye; Kim, Chanwoong; Noh, Hyun; Eo, Eunkyung (Clinical and experimental emergency medicine, 2022)
Objective The purpose of this study was to analyze the current situation concerning professionalism among emergency physicians in South Korea by conducting a survey regarding their perceptions and experiences of unprofessional behavior.Methods In October 2018, the authors evaluated the responses to a questionnaire administered to 548 emergency physicians at 28 university hospitals. The participants described their perceptions and experiences concerning 45 unprofessional behaviors classified into the following five categories: patient care, communication with colleagues, professionalism at work, research, and violent behavior and abusive language. Furthermore, the responses were analyzed by position (resident vs. faculty). Descriptive statistics were generated on the general characteristics of the study participants. To compare differences in responses by position and sex, the chi-square and Fisher exact tests were performed.Results Of the 548 individuals invited to participate in this study, 253 responded (response rate, 46.2%). In 34 out of 45 questionnaires, more than half of participants reported having experienced unprofessional behavior despite their negative perceptions. Eleven perception questions and 38 experience questions for unprofessional behavior showed differences by position.Conclusion Most emergency physicians were well aware of what constituted unprofessional behavior; nevertheless, many had engaged in or observed such behavior.